Alternative UNC13D Promoter Encodes a Functional Munc13-4 Isoform Predominantly Expressed in Lymphocytes and Platelets - Galgano, Donatella; Soheili, Tayebeh; Voss, Matthias; Torralba-Raga, Lamberto; Tesi, Bianca; Cichocki, Frank; Andre, Isabelle; Rettig, Jens; Cavazzana, Marina; Bryceson, Yenan (Frontiers in Immunology, 2020)
Autosomal recessive mutations in genes required for cytotoxicity are causative of a life-threatening, early-onset hyperinflammatory syndrome termed familial hemophagocytic lymphohistiocytosis (FHL). Mutations in UNC13D cause FHL type 3. UNC13D encodes Munc13-4, a member of the Unc13 protein family which control SNARE complex formation and vesicle fusion. We have previously identified FHL3-associated mutations in the first intron of UNC13D which control transcription from an alternative transcriptional start site. Using isoform specific antibodies, we demonstrate that this alternative Munc13-4 isoform with a unique N-terminus is preferentially expressed in human lymphocytes and platelets, as compared to the conventional isoform that was mostly expressed in monocytes and neutrophils. The distinct N-terminal of the two isoforms did not impact on Munc13-4 localization or trafficking to the immunological synapse of cytotoxic T cells. Moreover, ectopic expression of both isoforms efficiently restored exocytosis by FHL3 patient-derived Munc13-4 deficient T cells. Thus, we demonstrate that the conventional and alternative Munc13-4 isoforms have different expression pattern in hematopoietic cell subsets, but display similar localization and contribution to T cell exocytosis. The use of an alternative transcriptional starting site (TSS) in lymphocytes and platelets could be selected for increasing the overall levels of Munc13-4 expression for efficient secretory granule release.